Back Cover: A Facile Synthesis of High‐Surface‐Area Sulfur–Carbon Composites for Li/S Batteries (Chem. Eur. J. 28/2015). Issue 28 (6th July 2015) - Kaiser, Mohammad Rejaul; Liang, Xin; Konstantinov, Konstantin; Liu, Hua‐Kun; Dou, Shi‐Xue; Wang, Jia‐Zhao
<x xml:space="preserve">Abstract</x> The newly developed spray precipitation method for fabrication of sulfur–carbon composites is a facile method, in which sodium thiosulfate solution is sprayed onto an oxalic acid solution that contains carbon black (CB), producing a homogeneous mixture of CB and sulfur. Elemental sulfur is not only precipitated on the CB particles, but is also covered by other CB particles leading to a conductive 3D network and facilitating the utilization of insulating sulfur as a cathode material in Li/S batteries. Sulfur, which is a green material, has a very high energy density and is considered as a potential material for large batteries for storing renewable energies (e.g., wind, solar power). For more information, see the Full Paper by K. Konstantinov, J.‐Z. Wang and co‐workers on page 10061 ff.